Advances in Production and Industrial Engineering (University of Maribor Press, 2017)
This publication, scientific monograph, offers comprehensive chapter series from scientific researchers conducted by regional authors, authorities in the fields and summarizes the principal scientific contributions. The chapters deal with range topics from optimization techniques in production development, quality in production processes, product and process development, technologies for business development and factors of social and economic development. Edited by two editors with contributions from chapters’ authors, this scientific monograph presents advanced topics for students, educators and practitioners. The editors would like to thank all chapters’ authors for devoting of the research results and expertise with the great enthusiasm. We encourage all of them to continue successful highly valuable cooperation, between Faculty of Mechanical Engineering at the University of Maribor and Faculty of Mechanical Engineering at the Ss. Cyril and Methodius University in Skopje.